The Role of Teacher–Student Relationships in Predicting Teachers’ Occupational Wellbeing, Emotional Exhaustion, and Enthusiasm - Cui, Liying (Frontiers in Psychology, 2022)
Well-being is regarded as a core dimension of an individual’s prosperity in the field of positive psychology. Underlying this multifaceted framework are emotive, mental, and societal forms of well-being, which can be based on constructive connections in the workplace. Career well-being among educators is linked to optimal mental functioning and their constructive career experience is characterized in terms of the existence of constructive dimensions like enthusiasm at the workplace. Emotive exhaustion or fatigue, however, is a central element in the research on educator burnout and has an important effect on educators’ expert lives. Alternatively, the excellence of teacher-student relationships is significant in the process of language learning so this review tries to focus on the prominence of teacher-student relationships for the teachers’ well-being. The results from the review of the literature specified that high-value teacher-student relationships keep educators away from being emotionally exhausted since it can enhance the quantity of enthusiasm and lessen the amount of exhaustion. In a nutshell, this review of literature has suggestions for academics and experts in search of increasing teachers’ occupational well-being.